TINJAUAN KONDISI FISIK PADA ATLET KARATE PUSAT PENDIDIKAN DAN LATIHAN PELAJAR DISPORA RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Physical fitness is an important element and becomes the basis for developing techniques, tactics and strategies in karate. Some of the physical conditions that a karate athlete must have are stamina, strength, speed, agility, and flexibility. The purpose of this study was to determine the level of physical fitness of the PPLP Dispora Riau athletes, including endurance, arm muscle strength, abdominal strength, speed, agility and flexibility. The subjects of this study were 10 PPLP Riau Dispora Karate athletes. The results of the research: (1) Durability of karate athletes PPLP Dispora Riau averaged 45 ml/kg/min. (2) Strength of arm and shoulder muscles of PPLP Dispora Riau athletes averaged 4.81 kg / second. (3) The speed of the karate athletes of the Riau Dispora PPLP was 4.66 /second. (4) The flexibility of the PPLP Riau Dispora karate athletes was 21.2 cm. (5) The karate athletes' agility at PPLP Dispora Riau averaged 13.90 seconds. Thus, from the results of this research, it can be concluded that the physical condition of the PPLP Dispora Riau karate athletes is in excellent condition, namely agility and flexibility, while the strength of the arm and shoulder muscles fall into the category of sufficient, endurance, speed respectively in the category less good and lessKey Words: Physical Condition, Karate